Deliverance from hunger; public distribution system in India - Venugopal, K R (New Delhi, 1992)
This addition is about the literature on India's food and agricultural economy. The book is replete with data and detail which should serve as a handy reference to any student of the subject.'
Keywords: Food relief - India